1993
DOI: 10.1007/bf01952610
|View full text |Cite
|
Sign up to set email alerts
|

De novo biosynthesis of linoleic acid in two non-insect invertebrates: The land slug and the garden snail

Abstract: Abstract. The de novo biosynthesis of linoleic acid [18:2(n-6)], a fatty acid considered to be essential for most animals, was demonstrated in the land snail, Bulimulis alternatus mariae, and the garden slug, Arion circumscriptus.Radiolabeled acetate injected into the animals was incorporated into both 18:2 and 20:2, as demonstrated by radio-high performance liquid chromatography (radio-HPLC) and radio-gas chromatography (radio-GC). GCmass spectrometry (GC-MS) of the methoxy derivatives of the 18:2 and 20:2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…The FA biosynthesis pathways have been investigated in both terrestrial (van der Horst 1973(van der Horst , 1974Weinert et al 1993;Zhu et al 1994) and aquatic mollusc species (Chu and Greaves 1991;de Moreno et al 1976;Waldock and Holland 1984;Zhukova 1986Zhukova , 1991Zhukova , 2007Delaporte et al, 2005). It was shown that some molluscs have active FA elongation systems (Waldock and Holland, 1984;Zhukova, 1986;Delaporte et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The FA biosynthesis pathways have been investigated in both terrestrial (van der Horst 1973(van der Horst , 1974Weinert et al 1993;Zhu et al 1994) and aquatic mollusc species (Chu and Greaves 1991;de Moreno et al 1976;Waldock and Holland 1984;Zhukova 1986Zhukova , 1991Zhukova , 2007Delaporte et al, 2005). It was shown that some molluscs have active FA elongation systems (Waldock and Holland, 1984;Zhukova, 1986;Delaporte et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that animals desaturate fatty acids using A9 desaturase, 1 6 0 and 18:O being at the base of desaturations and further elongations occurring via 16:107 and 18:lw9 synthesis (Gurr & James 1980). In contrast, plants are capable of A12 and A15 desaturations and thus constitute the main source of 0 3 and 0 6 PUFAs which are considered to be essential for animals (Gurr & James 1980, Sargent et al 1987Sargent et al , 1990 Weinert et al 1993). Although the enzyme responsible for this peculiar desaturation has not been investigated, Weinert et al (1993) supposed that these terrestrial gastropods use the same pathway as plants and some insects, based on a A12 desaturation of oleic acid (Cripps et al 1990, Borgeson et al 1991.…”
Section: Hydrothermal Gastropod Metabolismmentioning
confidence: 99%
“…In contrast, plants are capable of A12 and A15 desaturations and thus constitute the main source of 0 3 and 0 6 PUFAs which are considered to be essential for animals (Gurr & James 1980, Sargent et al 1987Sargent et al , 1990 Weinert et al 1993). Although the enzyme responsible for this peculiar desaturation has not been investigated, Weinert et al (1993) supposed that these terrestrial gastropods use the same pathway as plants and some insects, based on a A12 desaturation of oleic acid (Cripps et al 1990, Borgeson et al 1991. Compared to other marine heterotrophic invertebrates, such as bivalve molluscs or crustaceans (Ackman et al 1971, Ackman & Hooper 1973, Dall et al 1991 or symbiotic mussels from the same hydrothermal site (Pranal 1995, Pranal et al in press), A. hessleri and Ifremeria nautilei display particularly high levels of linoleic acid in their tissues.…”
Section: Hydrothermal Gastropod Metabolismmentioning
confidence: 99%
“…Exceptions include those species of insects (Blomquist et al, 1982;Cripps et al, 1986) and other invertebrates (Weinert et al, 1993) which are able to biosynthesize 18:2n-6 from 18:1n-9 by action of a Δ-12 desaturase (fatty acid notation described in Stanley-Samuelson et al, 1988;Stanley, 2004). PUFAs act in two areas of animal biology.…”
Section: Introductionmentioning
confidence: 99%